1973
DOI: 10.3758/bf03214124
|View full text |Cite
|
Sign up to set email alerts
|

Comparing objects in memory: Evidence suggesting an internal psychophysics

Abstract: In this experiment, Ss were visually presented with the names of two animals and were required to throw a switch under the name of the larger animal. Although error rates were relatively low (4.5%), reaction time (RT) was largely an inverse linear function of the logarithm of the estimated difference in animal size. Since RT is similarly related to size differences when Ss make direct perceptual comparisons (e.g.. of lengths of line), it was argued that Ss compare animal names by making an "internal psychophys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

28
248
1
6

Year Published

1975
1975
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 372 publications
(283 citation statements)
references
References 8 publications
28
248
1
6
Order By: Relevance
“…This notion goes back at least to Moyer (1973), who referred to an ''internal psychophysics'' for symbolic comparisons. Behavioral studies have identified striking parallels between symbolic distance effects and those observed in overt perceptual comparisons (e.g., Holyoak & Patterson, 1981;Moyer & Bayer, 1976).…”
Section: Alternative Models Of Symbolic Magnitude Comparisonsmentioning
confidence: 99%
See 1 more Smart Citation
“…This notion goes back at least to Moyer (1973), who referred to an ''internal psychophysics'' for symbolic comparisons. Behavioral studies have identified striking parallels between symbolic distance effects and those observed in overt perceptual comparisons (e.g., Holyoak & Patterson, 1981;Moyer & Bayer, 1976).…”
Section: Alternative Models Of Symbolic Magnitude Comparisonsmentioning
confidence: 99%
“…In particular, both perceptual and symbolic judgments yield a distance effect, such that the ease of judgments (indexed by accuracy and/or reaction time) increases with the magnitude difference between the objects being compared (e.g., Moyer, 1973;Moyer & Bayer, 1976;Moyer & Landauer, 1967). A symbolic distance effect is observed not only with quasi-perceptual dimensions such as size, but also with more abstract dimensions such as animal intelligence (Banks, White, Sturgill, & Mermelstein, 1983) and with scalar adjectives of quality (e.g., good, fair; Holyoak & Walker, 1976).…”
Section: Introductionmentioning
confidence: 99%
“…It can be seen that RTs generally decreased as the size difference increased. thus replicating the general function obtained by Moyer (1973). In addition.…”
Section: Methodsmentioning
confidence: 99%
“…Each type included three pairs from each of six different larger/smaller size ratios, namely, 1.17, lAO, 1.75, 2.33, 3.50, and 7.0. These were selected so as to sample the range of size differences used in Moyer's (1973) experiment. with the sampled differences converted into ratios according to the normative ratings in Table I of the present study.…”
Section: Methodsmentioning
confidence: 99%
“…This finding, called the distance effect, was previously found in perceptual comparisons of various materials, for example, the length of bars (Johnson, 1939). Since then, it has been reproduced many times with miscellaneous materials: digits (Banks, Fujii, & Kayra-Stuart, 1976;Buckley & Gilman, 1974;Parkman, 1971;Sekuler & Mierkiewicz, 1977;Sekuler, Rubin, & Armstrong, 1971; see also Restle, 1970), two-digit numbers (Hinrichs, Yurko, & Hu, 1981), dot arrays compared for numerosity (Buckley & Gilman, 1974), objects indicated by name and compared for size (Holyoak, 1977;Kosslyn, Murphy, Bemesderfer, & Feinstein, 1977;Moyer, 1973), and abstract orderings with no physical counterpart (Woocher, Glass, & Holyoak, 1978). One particularly compelling experiment (Buckley & Gilman, 1974) should be noted, in which the same subjects were tested in two different paradigms: comparison of numerosities and comparison of digits.…”
Section: Is Numerical Comparison Digital? Analogical and Symbolic Effmentioning
confidence: 99%